A comparative analysis of information sources about the prevalence of congenital anomalies of Lithuanian children - Židanavičiūtė, Jurgita; Radavičius, Marijus; Sušinskas, Jurgis; Utkus, Algirdas (Lietuvos matematikos rinkinys, 2003)
The work is based on data from two data bases containing information about the prevalence of congenital anomalies of Lithuanian children. The first one is collected from autopsy data by one of the authors and covers the period 1981–1991. The second, called LIRECA, is maintained since 1993 and is based on questionnares filled in for each case of congenital anomaly of new-born. It is supposed that through absence of financial support this data base do not lately reflect the real situation. The aim of the work is to check this hypothesis on the ground of the comparative analysis of the both data bases and to estimate the extent of the disagreement.